Tri6 encodes an unusual zinc finger protein involved in regulation of trichothecene biosynthesis in Fusarium sporotrichioides. - Proctor, R H (1995)
In Fusarium sporotrichioides, several genes required for biosynthesis of the trichothecene mycotoxin T-2 toxin are closely linked. Further characterization of this gene cluster has revealed a gene, Tri6, that specifies a 217-amino-acid protein with regions similar to Cys2His2 zinc finger proteins. Temporal expression of Tri6 is similar to that of trichothecene biosynthetic pathway genes. Analysis of Tri6 transcripts indicated that transcription is initiated in two regions and that within each region there may be at least four initiation sites. Disruption of Tri6 resulted in a mutant that did not produce trichothecenes but that did accumulate low levels of the trichothecene precursor trichodiene. The Tri6 mutant was unable to convert six trichothecene biosynthetic intermediates to T-2 toxin, and transcription of two biosynthetic genes, Tri4 and Tri5, was greatly reduced in the mutant relative to the wild type. In addition, the product of Tri6 functioned as a transcriptional activator in Saccharomyces cerevisiae when fused to the DNA binding region of GAL4. These results indicate that Tri6 encodes a protein involved in the transcriptional regulation of trichothecene biosynthetic genes in F. sporotrichioides.